AWARENESS OF POTENTIAL AMBIENT RADON GAS INHALATION HAZARDS AMONG UNDERGRADUATE STUDENTS AND STAFF OF A MEDICAL SCHOOL IN SOUTH-EAST, NIGERIA (Journal of Biomedical Investigation, 2023)
Background: Radon is a noble radioactive gas considered as one a significant ambient indoor air pollutant and eminently associated with lung carcinoma. There is paucity of research on knowledge and awareness of ambient inhalation of radon gas and associated potential radiological hazards among health workers.Aim: This study aimed at assessing the awareness of potential ambient radon gas inhalation hazards among undergraduate students and staff of students and staff of College of Health Sciences, Nnamdi Azikiwe University.Materials and Methods: This cross-sectional study involved students and staff of College of Health Sciences, Nnamdi Azikiwe University, using a questionnaire. A 20-item semi-structured questionnaire was administered to 550 participants (undergraduate students, academic staff and non-academic staff). Information on demographic characteristics of the respondents, knowledge of radon gas and radiological effects hazards were collected. The obtained data were summarized using descriptive statistics.Results: Majority of the participants were female 300 (54%). Most of the respondents 415 (75.5%) had no knowledge of Radon gas and have not even heard about it before this study. Only respondents 135 (24.5%) had knowledge of Radon gas before. Most of the respondents 448 (81.5%) were not aware that Radon gas is ionizing radiation of natural origin. Most participants 430 (78.2%) were not aware that Radon gas can cause serious health hazards to the Deoxyribonucleic acid (DNA) and can potentially cause lung cancer to the general population.Conclusion: Poor knowledge and awareness of ambient Radon gas and associated potential health hazards due to inhalation were eminent among students and staff of the College of Health Sciences, Nnamdi Azikiwe University.
Keywords: Knowledge; Awareness; Radon; Radiation; Radiological Hazards